Murine macrophage-based iNos reporter reveals polarization and reprogramming in the context of breast cancer - Mas-Rosario, Javier A.; Medor, Josue D.; Jeffway, Mary I.; Martínez-Montes, José M.; Farkas, Michelle E. (Frontiers in Oncology, 2023)
As part of the first line of defense against pathogens, macrophages possess the ability to differentiate into divergent phenotypes with varying functions. The process by which these cells change their characteristics, commonly referred to as macrophage polarization, allows them to change into broadly pro-inflammatory (M1) or anti-inflammatory (M2) subtypes, and depends on the polarizing stimuli. Deregulation of macrophage phenotypes can result in different pathologies or affect the nature of some diseases, such as cancer and atherosclerosis. Therefore, a better understanding of macrophage phenotype conversion in relevant models is needed to elucidate its potential roles in disease. However, there are few existing probes to track macrophage changes in multicellular environments. In this study, we generated an eGFP reporter cell line based on inducible nitric oxide synthase (iNos) promoter activity in RAW264.7 cells (RAW:iNos-eGFP). iNos is associated with macrophage activation to pro-inflammatory states and decreases in immune-suppressing ones. We validated the fidelity of the reporter for iNos following cytokine-mediated polarization and confirmed that reporter and parental cells behaved similarly. RAW:iNos-eGFP cells were then used to track macrophage responses in different in vitro breast cancer models, and their re-education from anti- to pro-inflammatory phenotypes via a previously reported pyrimido(5,4-b)indole small molecule, PBI1. Using two mouse mammary carcinoma cell lines, 4T1 and EMT6, effects on macrophages were assessed via conditioned media, two-dimensional/monolayer co-culture, and three-dimensional spheroid models. While conditioned media derived from 4T1 or EMT6 cells and monolayer co-cultures of each cancer cell line with RAW:iNos-eGFP cells all resulted in decreased fluorescence, the trends and extents of effects differed. We also observed decreases in iNos-eGFP signal in the macrophages in co-culture assays with 4T1- or EMT6-based spheroids. We then showed that iNos production is enhanced in these cancer models using PBI1, tracking increased fluorescence. Collectively, this work demonstrates that this reporter-based approach provides a facile means to study macrophage responses in complex, multicomponent environments. Beyond the initial studies presented here, this platform can be used with a variety of in vitro models and extended to in vivo applications with intravital imaging.